Partnership as a "Lever for Transformation": County-Level Leadership to Advance Systemic Social and Emotional Learning. - Cirolia, Alagia J; Hwang, Sophia H J; Michel, Esmeralda M; Committee, CalHOPE Research (Children & Schools, 2026)
Social and emotional learning (SEL) promotes student academic achievement and well-being. Social workers are well positioned to leverage their cross-sector, multilevel skill set for providing SEL implementation leadership. Leadership plays a critical role in achieving high-quality SEL implementation in classrooms, schools, and districts. However, there are no empirical studies of SEL leadership above the district level, limiting social workers' ability to leverage all levels of the education system, including counties and states, to take SEL to scale. This study explores who provides county-level SEL implementation leadership, why county-level leaders partner for SEL implementation, and how they cultivate partnerships in the context of a statewide effort to advance SEL. To conduct the study, county SEL implementation plans were analyzed using qualitative content analysis. Plans indicated that county-level implementation leadership was provided by people across levels of the education system, sectors, and regions, and by people from nongovernmental entities. Plans indicated that partnerships were intended to integrate SEL with aligned efforts, seek multiple perspectives on implementation, and expand the capacity for SEL implementation. SEL leaders intended to cultivate partnerships through relationship building and collaboration structures. Similarities and differences noted in county-level SEL implementation leadership, in comparison with school and district levels, are discussed alongside practice implications.